Investigation Of Time-Of-Flight (TOF) Imaging System During Deep Inspiration Breath-Hold Radiotherapy (DIBH-RT) For Left Breast Cancer Patients - Auwal, Abu Bakar (2022)
Deep inspiration breath-hold radiotherapy (DIBH-RT) pushes the heart away from treatment field thereby reducing the cardiac dose by over 50%. However, poor reproducibility and stability of the breath-hold during DIBH-RT treatment delivery could jeopardise the treatment success. The purpose of this work was to study the application of a Time-of-Flight (ToF) imaging system for monitoring breath-hold during DIBH-RT. Argos P330 3D ToF Camera (Bluetechnix Austria) was characterised by imaging an ISOCube phantom to assess the ToF measurement stability in conjunction with CBCT. Subsequently, the ToF imaging was performed on a total of 13 DIBH-RT patients during setup verification with CBCT imaging. Chest surface displacements were estimated from each modality and compared to validate the ToF measurement.